ASSOCIATION OF PHYSICAL AND NEUROPSYCHIATRIC MORBIDITIES WITH THE SEVERITY AND MORTALITY OF COVID-19 PATIENTS IN PAKISTAN - Khalid, Beenish; Farukh, Sadia; Kumar, Ashokh; Baig, Saeeda (Journal of Pakistan Psychiatric Society, 2024)
Objective: This study aimed to find out the association of co-morbidities; risk factors and complications, with the severity and mortality of Covid-19 patients in our set of population Methodology: Covid-19-positive patients (151) ages 18-80, were recruited, (June 2022 to May 2023) from Ziauddin Hospital, after informed consent and approval from Ethics Committee. The questionnaire recorded patients’ demographic variables, laboratory investigations, past medical history, and family history. Follow-up co-morbidities, recovery, death, or LAMA (Leave Against Medical Advice) data was taken from hospital records. Analyses were done using (SPSS) software. P-values of <0.05 were considered significant. Results: Out of 151 patients; females were 56 (37%) and males 95 (63%). Among these 82(54.3%) recovered, 52(34.4%) passed away and 17(11.2%) LAMA. Deaths in males 40(26.4%), were higher, compared to females 12(7.9%). Overall 84 (56%), suffered severe infection, 24 (16%) moderate and 43 (28%) mild. The most common risk factors were complications of the heart (hypertension) 35(42.7) followed by diabetes 27 (32.9) (p<0.001). Neuropsychiatric manifestations such as depression 36(23.8), was highest among post covid-19 complications, 14 (17.07%) patients had stroke out of which 9(17.3) could not survive. The most common cause leading to covid 19 severity was Pneumonia 76(80%) then diabetes 63(80%) and hypertension 69(78%) (p<0.001). Majority of patients, 88(58.3%) were above 50 years of age, 35(23.2%) between 25-50 and 28(185%) <25 years. Conclusion: The most common risk factor of Covid-19 were complications of the heart and diabetes. Highest post covid-19 complication among survivors was depression. The highest complication leading to death was Pneumonia.